GENE-08. SCHWANNOMATOSIS SCHWANNOMAS HARBOR DISTINCT DNA METHYLATION PROFILES. (5th November 2018) - Mansouri, Sheila; Paganini, Irene; Karimi, Shirin; Suppiah, Suganth; Mamatjan, Yasin; Singh, Olivia; Stemmer-Rachamimov, Anat; Papi, Laura; Aldape, Kenneth; Zadeh, Gelareh
Abstract: Schwannomas are characteristic manifestations of NF2 and schwannomatosis syndromes. However, the majority of schwannomas are solitary and sporadic. It is unclear whether and to what extent sporadic and syndrome-associated schwannomas or their histologic subtypes represent distinct biological groups. Clinically, although schwannomatosis schwannomas are considered benign, the majority of patients experience unmanageable pain; however, the underlying mechanism of this pain is not well understood. There is increasing evidence for DNA methylation profiling being able to distinguish biologically relevant tumor subgroups, even within the same cellular lineage and histopathologically similar tumors. In this study, we used Illumina Methylation EPIC arrays for methylome-based characterization of 88 schwannomatosis schwannomas, in comparison to 90 sporadic schwannomas and 14 NF-2 schwannomas. We performed unsupervised hierarchical clustering selecting 30, 000 probes that showed the highest median absolute deviation (MAD) across all beta values. Three different clustering sets were utilized to obtain the most refined differentiation. Schwannomatosis schwannomas formed 3 distinct methylome-based subgroups, which were fully distinct from sporadic schwannomas and NF-2 schwannomas. Additionally, we performed copy number analysis using the DNA methylation data to infer gross chromosomal deletions or gains among the sporadic and syndromic schwannomas, in addition to schwannomas with hybrid features. Methylation subgroups were further correlated with clinical parameters including age, gender, anatomic location, tumor size, germline mutation status (LZTR1/SMARCB1), and 22q LOH, in addition to the histopathologic features associated with each tumor. Furthermore, RNA sequencing was performed to examine gene expression profiles associated with the 3 methylome subgroups and the data was integrated with DNA methylation profiles to establish the biological relevance of hypo- and hyper-methylation of the top varying CpG sites. Cumulatively, these data will be correlated with the extent and type of pain experienced by schwannomatosis patients to elucidate the underlying mechanism of pain.